The Effect of Managerial Ownership, Information Asymmetry, Leverage, Company Size, and Bonus Compensation on Earnings Management: A Case Study of Manufacturing Companies in the Miscellaneous Industrial Sector Listed on the IDX in 2018-2023 - Devi Mayleani; Yunita Fitria (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to test and analyze the influence of managerial ownership, information asymmetry, leverage , company size and bonus compensation on earnings management. This study is a type of quantitative research with a population of manufacturing companies in various industries listed on the Indonesian Stock Exchange (IDX) in the observation period from 2018 to 2023. The sampling technique in this study used the purposive sampling method and the 20 companies were obtained in a period of six years so that 120 company data were obtained for the period 2018-2023. In this study, the data used are secondary data and hypothesis testing usung the regression analysis method with analysis tool, namely IBM SPSS Statistics 25 program. The results of this study indicate that (1) manegerial ownership has a positive not significant effect on earnings management, (2) information asymmetry has a positive and significant effect on earnings management, (3) Leverage  has a negative and significant effect on earnings management, (4) company size has a negative and significant effect on earnings management, (5) bonus compensation has a negative and significant effect on earnings management